2019
DOI: 10.1108/apjml-01-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Vlog and brand evaluations: the influence of parasocial interaction

Abstract: Purpose The purpose of this paper is to investigate the marketing results of video blogging (vlogging). In particular, the authors are interested in understanding which video bloggers (vloggers) can better help marketers develop their brand image, which vlog viewers tend to evaluate vlogger-endorsed brands more positively, and how these effects occur. Design/methodology/approach A questionnaire survey was conducted with a convenience sample online. A total of 401 valid responses were collected. Regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 74 publications
3
120
0
11
Order By: Relevance
“…(2017) found that attitudes toward eWOM influenced travelers' intentions to follow the advice of experienced professionals in the tourism industry. Viewers with stronger motives (conceptualized as perceived enjoyment felt by watching vlogger presentations) tend to pay more attention to videos with the same content, which makes them feel connected with the vloggers and other viewers (Liu et. al., 2019).…”
Section: Perceived Enjoymentmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017) found that attitudes toward eWOM influenced travelers' intentions to follow the advice of experienced professionals in the tourism industry. Viewers with stronger motives (conceptualized as perceived enjoyment felt by watching vlogger presentations) tend to pay more attention to videos with the same content, which makes them feel connected with the vloggers and other viewers (Liu et. al., 2019).…”
Section: Perceived Enjoymentmentioning
confidence: 99%
“…al., 2015;Mummumi et. al., 2019), hotel mobile apps (Seonjeong Lee, 2018), cosmetic products on social media platforms (Liu et. al., 2019), and Millennial traveling without a travel agent's assistance .…”
Section: Introductionmentioning
confidence: 99%
“…Tidak dipungkiri media sosial mengalami perkembangan yang sangat pesat dan begitu popular di masyarakat. Dengan cepat pula media sosial ini menggantikan peran media tradisional yang lebih dulu hadir di masyarakat (Liu et al, 2019). Baik masyarakat perkotaan maupun masyarakat pedesaan, begitu akrab dengan media sosial.…”
Section: Pendahuluanunclassified
“…On YouTube, one type of SMI content is especially popular: video blogs (short: vlogs;Liu et al, 2019). The core characteristic of vlogs is an SMI talking to a camera about personal topics (Frobenius, 2011).…”
Section: Introductionmentioning
confidence: 99%